p120-catenin is essential for terminal end bud function and mammary morphogenesis - Kurley, Sarah J.; Hofmann, Ilse (Development, 2012)
Although p120-catenin (p120) is crucial for E-cadherin function, ablation experiments in epithelial tissues from different organ systems reveal markedly different effects. Here, we examine for the first time the consequences of p120 knockout during mouse mammary gland development. An MMTV-Cre driver was used to target knockout to the epithelium at the onset of puberty. p120 ablation was detected in approximately one-quarter of the nascent epithelium at the forth week post-partum. However, p120 null cells were essentially nonadherent, excluded from the process of terminal end bud (TEB) morphogenesis and lost altogether by week six. This elimination process caused a delay in TEB outgrowth, after which the gland developed normally from cells that had retained p120. Mechanistic studies in vitro indicate that TEB dysfunction is likely to stem from striking E-cadherin loss, failure of cell-cell adhesion and near total exclusion from the collective migration process. Our findings reveal an essential role for p120 in mammary morphogenesis.